Cupping Therapy for the Treatment of Migraine Headache: a systematic review and meta-analysis of clinical trials - Bushra Mohandes; Fatma Elsayed Ahmed Bayoumi; Aisha Abdulkarim AllahDiwaya; Maryam Salah Falah; Leen Hesham Alhamd; Razan Abid Alsawadi; Yipeng Sun; Aidi Ma; Idris Sula; Muhammad Candragupta Jihwaprani (Korean Pharmacopuncture Institute, 2024)
Objectives: Cupping therapy is a widely used complementary medicine for the treatment of migraine headaches globally. However, conflicting evidence exists on its effectiveness. To evaluate the safety and efficacy of cupping therapy in treating migraine headache disorder.Methods: Seven databases were systematically searched: PubMed/MEDLINE, Clinicaltrials. gov, Cochrane CENTRAL, ScienceDirect, ProQuest, SinoMed, and the National Science and Technology Library. The primary endpoints are the treatment success and the pain intensity reduction. The secondary endpoints were adverse events (AEs) risk and improvement in quality of life (QoL), which was based on the Migraine Disability Scale (MIDAS). Subgroup analyses were performed based on the cupping techniques (wet and dry cupping) and adjunctive complementary treatments (i.e. acupuncture and/or collateral pricking).Results: Eighteen trials out of 348 records were included, pooling 1,446 participants (n = 797 received cupping therapy). Treatment success was significantly higher among those with cupping therapy (risk ratio [RR] [95% CI] = 1.83 [1.52-2.21]); with significant improvement observed only with wet cupping (RR [95% CI] = 1.88 [1.53-2.30]). The adjunctive complementary therapy did not achieve a greater amplitude of treatment success compared to cupping therapy alone. Furthermore, cupping therapy showed significant pain reduction compared to baseline (standardized mean difference [SMD] [95% CI] = 0.55 [0.39-0.70]) and achieved fewer risks of AEs (RR [95% CI] = 1.88 [1.53-2.30]). However, cupping did not improve the overall QoL (MIDAS SMD [95% CI] = -0.79 [-3.55-1.98]).Conclusion: Cupping therapy was an effective complementary modality to treat migraine headaches. However, it did not demonstrate improvement in QoL (PROSPERO: CRD42024514509).